Is It Just About Physical Health? An Online Cross-Sectional Study Exploring the Psychological Distress Among University Students in Jordan in the Midst of COVID-19 Pandemic - Al-Tammemi, Ala’a B.; Akour, Amal; Alfalah, Laith (Frontiers in Psychology, 2020)
Background Since the spread of COVID-19 on a global scale, most of efforts at national and international levels were directed to mitigate the spread of the disease and its physical harm, paying less attention to the psychological impacts of COVID-19 on global mental health especially at early stages of the pandemic. Objectives This study aimed to assess and explore (i) The levels of psychological distress and its correlates (ii) Motivation for distance learning (iii) Coping activities and pandemic related concerns, among university students in Jordan in the midst of COVID-19 pandemic. Methods A cross-sectional study was conducted using an online self-administered questionnaire. The measure of psychological distress was obtained using the 10-item Kessler Psychological Distress Scale, while other questions have explored our study’s second and third aims. Results A total of 381 completed questionnaires were included in the analysis. Female participants slightly predominated the sample (n = 199, 52.2%). The respondents aged 18–38 years (mean 22.6 years, SD: 3.16). Concerning distress severity, most of respondents were regarded as having severe psychological distress (n = 265, 69.5%). 209 students (54.9%) reported that they had no motivation for distance learning. Ordinal logistic regression revealed a significant correlation between distress severity and many predictors. Among the predictors that were found to act as protective factors against higher levels of distress included older age (aOR = 0.64, P = 0.022; 95% CI: 0.44–0.94), and having a strong motivation for distance learning (aOR = 0.10, P = 0.048; 95% CI: 0.01–0.96). In contrary, being a current smoker (aOR = 1.99, P = 0.049; 95% CI: 1.10–3.39), and having no motivation for distance learning (aOR = 2.49, P = 0.007; 95% CI: 1.29–4.80) acted as risk factors for having higher levels of psychological distress among the students. The most common coping activity reported was spending more time on social media platforms (n = 269, 70.6%), and 209 students (54.9%) reported distance learning as their most distressing concern. Conclusion The COVID-19 pandemic and related control measures could impact the mental health of individuals, including students. We recommend a nationwide psychological support program to be incorporated into Jordan’s preparedness plan and response strategy in combating the COVID-19 pandemic.